Foundation of a subsidiary temple within Mahakal Temple complex - Temples of India Project Team (Jio Institute, 2024)
There is a foundation of another temple or subsidiary shrine on the left side corner in front of the entrance of the Mahakal shrine. Similar to the foundation in the right corner, this one also has a few surviving stairs. Adjacent to these steps, one can observe a stone stele.